Sistem Pendukung Keputusan Berbasis Web untuk Menentukan Guru Berprestasi Menggunakan Metode TOPSIS - Mulyana R, I Eka; Jatnika, Ema; Aulia Rahmat, Rinaldi Satia (JESII: Journal of Elektronik Sistem InformasI, 2025)
The most difficult thing in determining an outstanding teacher is the effort to eliminate the subjectivity factor so that every choice made is objective based on predetermined criteria. In order for the implementation of teacher selection to run, this makes the need for a decision support system that is able to provide assessment consistency with the application of normalization and provide convenience in the results of the scores that will be determined from each criterion. By applying the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method, it is possible to determine the best alternative by looking at the closest distance from the positive ideal solution and the farthest distance from the negative ideal solution. This system is also useful for schools in determining and calculating scores in determining teachers who are worthy of awards in the selection of outstanding teachers. This system has also been designed dynamically so that it can make it easier for school principals to determine criteria according to the school year. This is supported by the results of the system testing using beta conducted with 6 respondents, indicating that 83.3% of users agreed that the system was easy to use, while 66.6% considered the information provided satisfactory. This system effectively reduces subjectivity in decision-making and provides a faster and more efficient assessment process compared to the manual file-based selection method previously used at SMPN 9 Tasikmalaya.